Human leukocyte antigen associations in postural tachycardia syndrome - Shin, Yong‐Won (Ann Clin Transl Neurol, 2019)
Associations between human leukocyte antigen (HLA) and postural orthostatic tachycardia syndrome (POTS) have not been investigated. We included patients diagnosed with POTS and showing orthostatic heart rate increases ≥ 50 during orthostatic vital sign measurement or experiencing syncope/near‐syncope while standing (prominent POTS; n = 17). DQB1*06:09 was present in seven (41%) patients, a significantly higher percentage than in healthy Koreans (7%; odds ratio [OR] 8.7, 95% confidence interval [CI] 3.1–24.3, corrected P = 3.2 × 10(−4)) and epilepsy controls (8%; OR 7.9, 95% CI 2.7–23.5, corrected P = 3.2 × 10(−4)). Six (35.3%) carried the A*33:03‐B*58:01‐C*03:02‐DRB1*13:02‐DQB1*06:09 haplotype. The results signify an autoimmune etiology in prominent POTS.